The Stop-Only-While-Shocking algorithm reduces hands-off time by 17% during cardiopulmonary resuscitation – a simulation study. (December 2016) - Koch Hansen, Lars; Mohammed, Anna; Pedersen, Magnus; Folkestad, Lars; Brodersen, Jacob; Hey, Thomas; Lyhne Christensen, Nicolaj; Carter-Storch, Rasmus; Bendix, Kristoffer; Hansen, Morten R.; Brabrand, Mikkel
Abstract : Introduction: Reducing hands-off time during cardiopulmonary resuscitation (CPR) is believed to increase survival after cardiac arrests because of the sustaining of organ perfusion. The aim of our study was to investigate whether charging the defibrillator before rhythm analyses and shock delivery significantly reduced hands-off time compared with the European Resuscitation Council (ERC) 2010 CPR guideline algorithm in full-scale cardiac arrest scenarios. Methods: The study was designed as a full-scale cardiac arrest simulation study including administration of drugs. Participants were randomized into using the Stop-Only-While-Shocking (SOWS) algorithm or the ERC2010 algorithm. In SOWS, chest compressions were only interrupted for a post-charging rhythm analysis and immediate shock delivery. A Resusci Anne HLR-D manikin and a LIFEPACK 20 defibrillator were used. The manikin recorded time and chest compressions. Results: Sample size was calculated with an α of 0.05 and 80% power showed that we should test four scenarios with each algorithm. Twenty-nine physicians participated in 11 scenarios. Hands-off time was significantly reduced 17% using the SOWS algorithm compared with ERC2010 [22.1% (SD 2.3) hands-off time vs. 26.6% (SD 4.8); P <0.05]. Conclusion: In full-scale cardiac arrest simulations, a minor change consisting of charging the defibrillator before rhythm check reduces hands-off time by 17% compared with ERC2010 guidelines.